From the Frontline to the Homefront: The Experience of Israeli Veterans - Solomon, Zahava (Frontiers in Psychiatry, 2020)
The state of Israel was founded to provide a safe and secure homeland for the Jewish people after 2000 years of persecution and deportations in the diaspora. In Israel’s 72 years of existence, its inhabitants were unfortunately exposed to seven wars and countless terrorist’s attacks. Trauma is therefore not merely an academic, but rather an existential issue for Israelis. This unfortunate reality has turned Israel into a natural stress laboratory that enables systematic research on biopsychosocial effects traumatic stress on soldiers and civilians. This article reviews the findings of a series of studies that examine (a) the short and the long term mental health effects of war on combat veterans (b) the effects of repeated exposure to war on veterans (c) trajectories of PTSD and specifically(d) reactivation and (e) delayed onset PTSD. We present the findings of 2 decades of systematic trauma research, documenting the deep and enduring psychopathological effects of wars on veterans. As the war does not end when the shootings stop, its effects are carried from the front line to the home front. Consequently, traumatized veterans plight has ripple and contagious effects, traumatizing both their spouses and offspring. Both acute and chronic trauma multifaceted manifestations and trajectories will be presented. Clinical ramifications and implications will also be discussed.